Gold(I)‐Catalysed Hydroarylation of 1, 3‐Disubstituted Allenes with Efficient Axial‐to‐Point Chirality Transfer. Issue 27 (26th April 2018) - Sutherland, Daniel R.; Kinsman, Luke; Angiolini, Stuart M.; Rosair, Georgina M.; Lee, Ai‐Lan
Abstract: Hydroarylation of enantioenriched 1, 3‐disubstituted allenes has the potential to proceed with axial‐to‐point chirality transfer to yield enantioenriched allylated (hetero)aryl compounds. However, the gold‐catalysed intermolecular reaction was previously reported to occur with no chirality transfer owing to competing allene racemisation. Herein, we describe the development of the first intermolecular hydroarylations of allenes to proceed with efficient chirality transfer and summarise some of the key criteria for achieving high regio‐ and stereoselectivity. Abstract : Overcoming allene racemisation : Intermolecular hydroarylation of allenes with efficient axial‐to‐point chirality transfer has been developed for the first time by using gold(I) catalysis. A substrate scope is presented, along with suggested prerequisites for achieving excellent regio‐ and stereoselectivity.